Le lien familial au coeur du quotidien transnational: les femmes shi’ites libanaises à Montréal - Le Gall, Josiane (Anthropologica, 2022)
Lebanese Shi’ites living in Montreal reconfigure space in such a way that they can be said to be living simultaneously in Montreal and in Lebanon. Though very involved in the Montreal setting, they participate at a distance in Lebanese society, with the help of modern technology. Women are often neglected in writings on transnationalism, but our research shows Lebanese Shi’ite women involved on a daily basis in transnational ties. Their transnational practices must be understood in relation to models of the family in Lebanon as well as certain particularities of the women’s social relations in Montreal. Both contribute to intensifying the importance of contact with family members living Lebanon or other national contexts.